Cerebral lipiodol embolism following transcatheter arterial chemoembolization for hepatocellular carcinoma - Wu, Lu (The WJG Press and Baishideng, 2010)
Cerebral lipiodol embolism (CLE) is an extremely rare complication of transcatheter arterial chemoembolization for hepatocellular carcinoma (HCC). The authors present a case of CLE that occurred after the second hepatic arterial chemoembolization for HCC, and attempt to introduce several plausible mechanisms of CLE, after reporting the clinical and radiological findings and reviewing the medical literature.